The influence of attitudinal factors of SME owner-managers on adoption of financial products - Rasheed, Rabia; Abdul Rahman, Maria; Bhutta, Rashid (Universiti Utara Malaysia, 2017)
Given the key role of owner managers in the decision making process, understanding socio-psychological factors of small and medium enterprises (SMEs) financial behavior has often been prescribed as an important research direction.In accordance with the above, present study in context of Pakistan investigated the attitudinal factors of SMEs owner-managers’ towards adoption of financial products.The attitudinal factors are depicted as perceived relative advantage, perceived compatibility and perceived complexity.The proposed model has been adapted, which is composed of decomposed theory of planned behavior (DTPB) and decomposed attitudinal factors of SMEs owner-manager to investigate their intention to adopt financial products in Pakistan. Relying on a survey research design, and following stratified sampling method, after screening process 285 owner-managers responses have been considered for further analysis.The findings revealed that perceived relative advantage and perceived compatibility possess significant positive relationships with owner-manager attitude towards adoption of financial product which further significantly predicts behavioral intention.Moreover, perceived complexity has negative but significant relationship with SMEs owner-manager attitude towards adoption of financial products. SMEs owner-managers exhibit serious concern towards formal financial products adoption, the policy makers are suggested to focus on creating specialized products which are useful, compatible and easy to understand for SMEs owner-manager in Pakistan.